What if We Learnt Like a Garden? Learning Collective Agency through Permaculture - Schlieker, Anne; Blasco, Maribel; Dioba, Albina (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
This short article invites readers to glimpse an ongoing learning experiment through which we prototype a future-oriented pedagogy aimed at cultivating resilient forms of collective agency and innovation. The pedagogy draws on permaculture, a regenerative design framework focused on maximizing beneficial relationships in nature, and is enacted in Permahaven, a living lab where we cultivate not only herbs and compost, but also regenerative thinking, collective agency, and a pedagogy grounded in joy and relationality. Permahaven provides an illustrative case of how permaculture principles can inform the design of learning environments that privilege collective over individualistic orientations and joy over instrumentalism. Such an approach strengthens learners’ collective agency as well as their ability to co-create more resilient socio-ecological futures.